Ministry Of Housing, Utilities And Urban Communities Ministerial Decree No. 954 of the Year 2022 = وزارة الإسكان والموافق والمجتمعات العمرانية قرار وزارى رقم 954 لسنة 2022 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic